Literature Survey of US Patents for Turbo Code - muhammad abdulhamid (CV. Akira Java Bulu, 2026)
Turbo codes are a class of high-performance forward error correction (FEC) codes used in information theory that were first published in 1993 but were developed between 1990 and 1991. They were the first working codes to get very close to the Shannon limit, also known as the maximum channel capacity, which is the highest theoretical code rate at which dependable communication is still feasible at a given noise level. In 3G/4G/5ذG mobile communications, turbo codes are utilized (e.g. in satellite communications, UMTS and LTE), and other applications where designers aim to accomplish dependable information transfer over communication links with limited bandwidth or latency in the presence of data-corrupting noise. In addition to outlining its structure, this paper offers a succinct explanation of how Turbo Code is used in US patents.